Evidence of Circulation of Several HAV Genetic Variants and Emergence of Potential Antigenic Variants in an Endemo-Epidemic Country before Vaccine Introduction - Kaouther Ayouni; Anissa Chouikha; Oussema Khamessi; Henda Touzi; Walid Hammemi; Henda Triki (Viruses, 2021)
Similar to several other countries in the world, the epidemiology of hepatitis A virus changed from high to intermediate endemicity level in Tunisia, which led to the occurrence of outbreaks. This study aimed to determine the genetic and antigenic variability of HAV strains circulating in Tunisia during the last few years. Genotyping using complete VP1 gene and VP1-2A junction confirmed the predominance of genotype IA, with co-circulation of several genetic and antigenic variants. Phylogenetic analysis including Tunisian and strains from other regions of the world showed the presence of at least two IA-variants within IA subgenotype. Amino-acid analysis showed several mutations in or close to epitope regions in the VP1-region. This study provides a baseline on the genetic and antigenic variability of HAV circulating strains before the introduction of vaccination into the national immunization schedule.